2008
DOI: 10.1007/s10803-007-0503-0
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Self-Presentation of Children with Autism Spectrum Disorders

Abstract: The self-presentational behaviour of 43 6- to 12-year-old children with high functioning autism spectrum disorders (HFASD) and normal intelligence and 43 matched comparisons was investigated. Children were prompted to describe themselves twice, first in a baseline condition and then in a condition where they were asked to convince others to select them for a desirable activity (self-promotion). Even after controlling for theory of mind skills, children with HFASD used fewer positive self-statements at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
4
22
2
1
Order By: Relevance
“…Many of them were aware of and at times concerned for their reputation, with some discussing specific changes in behaviour they had made to impress others. This finding supports previous research with adults with autism (Cage et al, 2013) and experimental research evidencing self-presentation skills in children with autism (Begeer et al, 2008;Scheeren et al, 2010). These studies evidence an awareness and concern for reputation in autism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Many of them were aware of and at times concerned for their reputation, with some discussing specific changes in behaviour they had made to impress others. This finding supports previous research with adults with autism (Cage et al, 2013) and experimental research evidencing self-presentation skills in children with autism (Begeer et al, 2008;Scheeren et al, 2010). These studies evidence an awareness and concern for reputation in autism.…”
Section: Discussionsupporting
confidence: 91%
“…Autistic individuals are known to struggle with automatically determining others' thoughts (Ruffman, Garnham & Rideout, 2001;Senju, Southgate, White & Frith, 2009) but may learn to master some perspective-taking skills (Bowler, 1992;Happé, 1995;Scheeren et al, 2013). There is also evidence that children with autism can self-promote (Begeer et al, 2008;Scheeren et al, 2010) -an ability that further suggests that autistic individuals may be somewhat concerned by how they are viewed by others. Furthermore, autistic adolescents are sensitive to social rejection: following ostracism in a cyber ball game, they were negatively affected in terms of anxiety, self-esteem and belonging, much like their typical peers (Sebastian, Blakemore & Charman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When informed that they may be selected for a prize-winning game based on their self-description typically developing (TD) children highlight their positive attributes and game-related abilities. In a study by Begeer et al (2008) children with ASD (6-12 years) also increased in positive statements about themselves, yet these statements were less related to their abilities or preferences in playing games. These findings suggest that children with ASD can be motivated to adjust their self-presentation, but they do so less strategically.…”
Section: Introductionmentioning
confidence: 89%
“…Based on these features, children with ASD are expected to be limited in their self-presentation skills. Empirical studies have indeed shown that children with ASD are less strategic in the way they present themselves compared to typically developing peers (Begeer et al 2008;Scheeren et al 2010). However, these studies relied on children's responses to hypothetical situations (Begeer et al 2008) or included relatively small samples (Scheeren et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation